Identification of mycobacterial bacterioferritin B for immune screening of tuberculosis and latent tuberculosis infection. (December 2017) - Yang, Xinyu; Wu, Jia-bao; Liu, Ying; Xiong, Yanqing; Ji, Ping; Wang, Shu-jun; Chen, Yingying; Zhao, Guo-ping; Lu, Shui-hua; Wang, Ying
Abstract: Objectives: It remains necessary and urgent to search for novel mycobacterial antigens to increase the sensitivity and specificity for tuberculosis (TB) diagnosis and latent TB infection (LTBI) screening. Antigens capable of inducing strong immune responses during Mycobacterium tuberculosis (M.tb) infection would be good candidates. Methods: Cellular responses specific to M.tb derived bacterioferritin B (BfrB) were assessed by IFN-γ ELISPOT in three human cohorts, including healthy controls (HCs), LTBI population and pulmonary TB (PTB) patients. Its significance in TB diagnosis and LTBI identification was further analyzed. Results: BfrB-specific IFN-γ responses in PTB and LTBI groups were significantly higher than that in HCs. However, BfrB-specific IFN-γ release was not as strong as that to ESAT-6 or CFP-10 in PTB patients whereas comparable in LTBI cohort with possible complementary properties to ESAT-6 or CFP-10. More interestingly, there were a considerable number of HCs with high BfrB-specific cellular responses. When HCs with high BfrB-specific cellular responses were subgrouped into ESAT-6/CFP-10 hi (SFUs = 3, 4, 5) and ESAT-6/CFP-10 lo (SFUs < 3) groups, those who belonged to ESAT-6/CFP-10 hi group exhibited higher PPD responsiveness than ESAT-6/CFP-10 lo group. Conclusions: PTB and LTBI groups exhibit higher BfrB-specific IFN-γ responses than HCs. Although BfrB is not as immunodominant as ESAT-6/CFP-10 during acute M.tb infection, comparable BfrB-specific cellular immune responses are observed in LTBI population with the potential to increase the sensitivity for LTBI screening. Moreover, strong BfrB-specific IFN-γ release in the healthy cohort is probably cautionary in identifying leaky LTBI from HCs. BfrB might thus be considered as an additional biomarker antigen for LTBI identification.